Exploring Dimension, Perceived Individual Tension and Capacity Building Measure of Women Empowerment in India - Reddy , K. Gayathri; P.S, Varsha; Rao, L.N Sudheendra; Kumar , Amit (Asian Journal of Empirical Research, 2019)
The objective of current study is to identify different dimensions of women empowerment, problems and challenges such as perceived tension of individual self -help group member in the process of women empowerment, and suggestions to improve women empowerment in the context of India. The 351 responses were collected via stratified random sampling from members of self -help groups, and an exploratory principal component analysis is undertaken to identify the number of components that underlie the women empowerment. Further, a confirmatory factor analysis is used to confirm the factors in the study. The findings indicate five broad dimensions (i.e. economic, political, social, legal, psychological), four different types of perceived individual tensions (i.e., economic, social, legal, technology-oriented learning), and four significant categories of capacity building measures (i.e. training on governance, technology-driven livelihood support, promoting networking, social justice & harmony) of women empowerment.